Kinetic study of the alkyl flavonoid ester prunin 6'-O-laurate synthesis in acetone catalysed by immobilised Candida antarctica lipase B - Celiz, Gustavo; Martearena, Maria Rita; Scaroni, Elsa Elda; Daz, Mirta Elizabeth (Biochemical Engineering Journal)
Alkyl prunin esters are new compounds, which are soluble in lipophilic media. They possess antioxidant and antibacterial properties, so they may have useful applications. The current work studied the kinetic of prunin 6'. -O-laurate synthesis catalysed by Novozym 435 from vinyl laurate and prunin in acetone completely solubilised, forming colloids or scattered in solid state, according to its concentration in the reaction media.The kinetic study was determined at 50°C using initial concentrations between 20 and 220mM for prunin and between 20 and 4000mM (solvent free system) for vinyl laurate. When prunin completely solubilised or forming colloids was used, a model based on mechanism ordered Bi Bi without inhibition, neither by alcohol nor acyl group, which was the best fit in the initial rate data. The determined model was used to simulate initial reaction rate and these values were plotted against the experimental data. The model was consistent with the experimental data (slope 0.97±0.01, R2 0.993, n=72), even on solvent-free systems. Fil: Celiz, Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Salta. Instituto de Investigaciones para la Industria Química. Universidad Nacional de Salta. Facultad de Ingeniería. Instituto de Investigaciones para la Industria Química; Argentina Fil: Martearena, Maria Rita. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Salta. Instituto de Investigaciones para la Industria Química. Universidad Nacional de Salta. Facultad de Ingeniería. Instituto de Investigaciones para la Industria Química; Argentina Fil: Scaroni, Elsa Elda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Salta. Instituto de Investigaciones para la Industria Química. Universidad Nacional de Salta. Facultad de Ingeniería. Instituto de Investigaciones para la Industria Química; Argentina Fil: Daz, Mirta Elizabeth. Consejo Nacional de ...